The Authoritarian Leadership on Educators' Competency Influence - Utami, Hidayati Puja Utami; Afrisca, Mentari; Perdana, Ressa Nada; Burhanuddin, Burhanuddin (International Research-Based Education Journal, 2021)
The Authoritarian Leadership Style adopted by the Principal as a leader in an educational institution will have an impact on the competence of educators, both positive and negative impacts.  Authoritarian leadership classically has a more structured relationship within an organizational scope, especially in directing the teaching staff under it as a whole and intact because there is no intervention in directing the direction of the institution.  This article aims to determine the impact manifested by the Principal's Authoritarian Leadership Style as the head of the agency and the relationship between authoritarian leadership style to the competence of the teaching staff.  This research method uses a literature study that describes previous research to find existing data and findings and present them in the discussion of the problems of this article.  The findings presented point to the emergence of negative and positive impacts and their relationship to the competence of educators in an educational institution that uses the Authoritarian Leadership Style of the Principal as the head of the agency.